Parental Acceptance of Moderate Sedation and Associated Techniques for Behavior Management in Saudi Arabia: A Cross-Sectional Study - Alanbari MA; Hamdan HM; Bawazir OA; Sulimany AM (Patient Preference and Adherence)
Mohamad A Alanbari,1 Hebah M Hamdan,2 Omar A Bawazir,1 Ayman M Sulimany1 1Department of Pediatric Dentistry and Orthodontics, College of Dentistry, King Saud University, Riyadh, Saudi Arabia; 2Department of Periodontics and Community Dentistry, College of Dentistry, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Mohamad A Alanbari, Pediatric Dentistry Department, Prince Sultan Military Medical City, Riyadh, Saudi Arabia, Email Mohdanbari91@gmail.comPurpose: This study aimed to evaluate the acceptance of moderate sedation (MS) as a behavior guidance technique (BGT) method among Saudi parents, and also assess their acceptance of other BGTs, including parental separation, papoose board (PB), and nitrous oxide (N2O), used in conjunction with MS.Patients and Methods: This cross-sectional study was conducted at the Dental University Hospital, King Saud University, Riyadh, Saudi Arabia. It involved Saudi parents of children aged 3– 5 years undergoing dental treatment with MS, alongside additional BGTs such as parental separation, PB, and N2O. Parents completed a questionnaire with demographic details and a post-treatment acceptance survey evaluating their satisfaction with the MS. Descriptive statistics were used for demographic information and parental acceptance. Chi-square and Fisher’s exact tests analyzed the association between parental acceptance and background characteristics.Results: A total of 85 parents were included in the study. Among these parents, 77 (90.59%) accepted MS, reporting minimal distress during dental treatment, and 78 (91.76%) would choose MS again. The PB received strong support from 79 (92.94%) of parents, with 83 (97.65%) finding it useful for child protection. However, 43 (50.59%) of parents felt uncomfortable with parental separation during therapy.Conclusion: Over 90% of Saudi parents showed high acceptance of MS and PB as BGTs. The study also revealed that 50.59% of parents were uncomfortable with being separated from their children during treatment. These findings highlight the need for strategies that can accommodate family involvement in pediatric dentistry, ultimately improving parental satisfaction.Keywords: child, dental anxiety, dental care, moderate sedation, parental acceptance, questionnaire